2019
DOI: 10.1002/ente.201901077
|View full text |Cite
|
Sign up to set email alerts
|

A Microtubular Direct Carbon Solid Oxide Fuel Cell Operated on the Biochar Derived from Pepper Straw

Abstract: Direct carbon solid oxide fuel cell (DC‐SOFC) is a promising energy conversion system, which can directly convert the chemical energy of biomass into electrical energy with high efficiency and low pollution. Herein, a microtubular DC‐SOFC fueled with the biochar derived from pepper straw for electrical power generation is reported. The DC‐SOFC operated on pepper straw char gives a maximum power density of 217 mW cm−2, comparable with 252 mW cm−2 for that with hydrogen fuel at 850 °C. Moreover, the lifetime of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Yu et al found that DC-SOFCs that were supplied by the biochar that was derived from a pepper straw achieved a maximum power density of 217 mW cm −2 . This is comparable to 252 mW/cm 2 , which is the power density of the hydrogen-fueled device at a temperature of 850 • C. Therefore, the results obtained by Yu et al demonstrate that the pepper-straw charcoal contains natural catalysts, which contribute to improving the electrochemical oxidation of solid fuels in DC-SOFCs [14][15][16][17].…”
Section: Introductionmentioning
confidence: 87%
“…Yu et al found that DC-SOFCs that were supplied by the biochar that was derived from a pepper straw achieved a maximum power density of 217 mW cm −2 . This is comparable to 252 mW/cm 2 , which is the power density of the hydrogen-fueled device at a temperature of 850 • C. Therefore, the results obtained by Yu et al demonstrate that the pepper-straw charcoal contains natural catalysts, which contribute to improving the electrochemical oxidation of solid fuels in DC-SOFCs [14][15][16][17].…”
Section: Introductionmentioning
confidence: 87%
“…When the SOFC and gasifier are operated separately, an equilibrium CO molar fraction benefits the cell performance because a higher CO concentration accounts for a higher cell performance according to Equation (20). This is not the case when the SOFC and fluidized bed are coupled together, as shown in Figure 7b-f.…”
Section: Low Activity Carbon Fuel Withmentioning
confidence: 98%
“…Compared with other fuel cells fed with gaseous fuel (such as H 2 , natural gas, CH 4 ), the exclusive characteristic of DC-SOFC is the solid fuel, which has a higher volumetric energy density. The solid fuel is convenient and safe to transport and can be obtained widely from coal [9][10][11][12][13][14][15] and biomass [3,16] (such as almond shells [17], wheat straw [18], corn cob char [19], pepper straw [20], and pomelo peel [21]). The concentration of solid fuel will not decrease due to the co-existence with gaseous products during the operation of the fuel cell, and thus the theoretical potential will not reduce.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows the network map of prominent researchers working on every aspect of DC-SOFC: electrodes, electrolyte, design, reaction process, and carbon fuel source. 20 Biochar.-The direct utilization of solid carbon in a fuel cell is a relevant innovation for electric power generation. The carbon fuel cell could offer significant advantages such as high energy conversion efficiency, minimization of Nitrogen Oxide emission due to its operating temperature range of 700 °C-1000 °C, and the production of a nearly pure CO 2 exhaust stream for direct CO 2 sequestration.…”
mentioning
confidence: 99%
“…Several biomass materials have the potential to be utilized as fuel for DC-SOFC in the form of biochar after undergoing pyrolysis. Biochar from pineapple peel and leaves, orange, cassava rhizome, durian peel, and corncob are being utilized as phosphate adsorbents, 27 adsorption potential for oxytetracycline, 20 carbon sequestration and soil amendment, 28 adsorptions, 29 material for utilization in poly(lactic) acid biocomposites, 30 and dye removal. 31 Although biochar has been the subject of innovation, they are yet to be explored as potential fuel for DC-SOFC in the quest for finding the best-suited biofuel for a specific type of anode material in the energy storage device.…”
mentioning
confidence: 99%